HUBUNGAN KOMUNIKASI PIMPINAN TERHADAP KINERJA KARYAWAN (STUDI PADA PT. PINK SERVICES INDONESIA CABANG BALI) - Laksminia Agustin, Ni Putu Jeni; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT Leadership is important part of communication in an organization for attaining the goals of the organization. Leadership communication is a form of assessment of an organization to know that organization has achieved the goal or not, we could see it through by employees’ performance. When organization’s leader can communicate well to the employees, it will affect the performance of the employees, so they can achieve the organization goal. This research intent to find out relation among the leadership communication on employees’ performance at PT. Pink Services Indonesia Branch Bali. This research uses quantitative method that is associative. In this research uses census or total sampling. The data is obtained by distributing questionnaires. In this research used the correlation Spearman Rank. The results reveal that found relation among the communication leadership on performance of employees at PT. Pink Services Indonesia Branch Bali. The direction of the relation between the communication leadership variables with employees’ performance at PT. Pink Services Indonesia Branch Bali depicted the same direction, it means that if the leader of company can communicate well with the employees, then the employees will show better performance. Keywords: Communication Leadership, Employee Performance